Fatigue and Sleep-Disordered Breathing in Multiple Sclerosis: A Clinically Relevant Association?. (22nd October 2013) - Kallweit, Ulf; Baumann, Christian R.; Harzheim, Michael; Hidalgo, Hildegard; Pöhlau, Dieter; Bassetti, Claudio L.; Linnebank, Michael; Valko, Philipp O.
Abstract : Background . Fatigue in patients with multiple sclerosis (MS) is highly prevalent and severely impacts quality of life. Recent studies suggested that sleep-disordered breathing (SDB) significantly contributes to fatigue in MS. Study Objective . To evaluate the importance of routine respirography in MS patients with severe fatigue and to explore the effects of treatment with continuous positive airway pressure (CPAP). Patients and Methods . We prospectively assessed the presence of severe fatigue, as defined by a score of ≥5.0 on the Fatigue Severity Scale (FSS), in 258 consecutive MS patients. Ninety-seven patients (38%) suffered from severe fatigue, whereof 69 underwent overnight respirography. Results . We diagnosed SDB in 28 patients (41%). Male sex was the only independent associate of SDB severity (P = 0.003 ). CPAP therapy in 6 patients was associated with a significant reduction of FSS scores (5.8 ± 0.5 versus 4.8 ± 0.6, P = 0.04 ), but the scores remained pathological (≥4.0) in all patients. Conclusion . Respirography in MS patients with severe fatigue should be considered in daily medical practice, because SDB frequency is high and CPAP therapy reduces fatigue severity. However, future work is needed to understand the real impact of CPAP therapy on quality of life in this patient group.